2021
DOI: 10.1103/physrevapplied.15.014041
|View full text |Cite
|
Sign up to set email alerts
|

Spin-VCSELs with Local Optical Anisotropies: Toward Terahertz Polarization Modulation

Abstract: We present a semi-classical model for spin-injected vertical-cavity surface-emitting lasers (spin-VCSELs) with local optical anisotropies. Particular focus is put on highly-anisotropic spin-lasers with broad application potential. A generalized matrix formalism for extraction of the laser modes is introduced, which enables to calculate spatial distribution of vectorial modes in arbitrary spin-VCSELs. Time-dependence of such laser modes is further studied using the generalized coupled mode theory (CMT). It is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 66 publications
(89 reference statements)
0
29
0
Order By: Relevance
“…Different parts for polariton based spin circuitry have already been realized 9,10,[20][21][22] with some recent exciting theoretical proposals 23,24 , but many challenges remain to be solved. Optical applications such as data communication or sensing benefit from precise control over a laser's polarization and modulation speeds, ideally using nonresonant excitation schemes like spin-VCSELs [25][26][27] . In this spirit, a great deal of effort has been devoted to generating sources of linearly polarized light such as colloidal nanorods 28 , materials with anisotropic optical properties 29 , quantum dots 30 , and optical parametric oscillators 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Different parts for polariton based spin circuitry have already been realized 9,10,[20][21][22] with some recent exciting theoretical proposals 23,24 , but many challenges remain to be solved. Optical applications such as data communication or sensing benefit from precise control over a laser's polarization and modulation speeds, ideally using nonresonant excitation schemes like spin-VCSELs [25][26][27] . In this spirit, a great deal of effort has been devoted to generating sources of linearly polarized light such as colloidal nanorods 28 , materials with anisotropic optical properties 29 , quantum dots 30 , and optical parametric oscillators 31 .…”
Section: Introductionmentioning
confidence: 99%
“…When the optical carrier remains after the polarization selective component, it causes cross talk at the stage of polarization hybrid coherent detection. Third, birefringence controls of spin-VCSELs including theoretical modeling are important for efficient generation of orthogonally-polarized modulation sideband with a high frequency [58][59][60][61][62]. Since the sensitivity of spin polarization modulation is subject to birefringence, efficient generation of an orthogonally-polarized modulation sideband requires birefringence control with accuracy in the order of a few gigahertz.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Amongst the proposed advantages of these devices over conventional lasers, the promise of very high speed operation [2] has recently excited much attention. It has been shown that high material birefringence can lead to frequency splitting [3] that enables ultra-fast polarisation modulation [4,5] and a possible route to a practical terahertz source [6]. The birefringence can be increased by applying strain [3][4][5], heating [7] or the incorporation of an integrated surface grating [8].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, however, this is an approximation since these anisotropies originate from interfacial, surface and strain effects within the VCSEL structure [19]. Hence a more accurate model to account for these non-local anisotropies is based on a matrix approach which yields the spatial distribution of the electromagnetic modes of the spin-VCSEL [6,20]. This model is particularly well suited also to model the effects of an integrated surface grating in order to tailor the high-speed performance of the device [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation